Interleukin 8 as a vaso-occlusive marker in Brazilian patients with sickle cell disease - Gonçalves,M.S. (2001)
Sickle cell disease has a worldwide distribution and is a public health problem in Brazil. Although vaso-occlusive crisis (VOC) is one of the most important clinical features of the disease, there are still several steps of its pathogenesis which are unknown. The increase of the chemotactic factor interleukin 8 (IL-8) has been reported to be involved in sickle cell disease crisis, but this has not been demonstrated conclusively. In the present study we analyzed serum IL-8 levels by ELISA and hematological parameters and hemoglobin patterns by standard techniques in 23 (21 SS and 2 SC) Brazilian patients with sickle cell syndromes during VOC caused by different inducing factors, 22 (21 SS and 1 SC) sickle cell patients out of crisis, and 11 healthy controls. Increased IL-8 levels were observed in 19 of 23 VOC patients (79.2%), 3 of them with more than 1,000 pg/ml. Seventeen of 22 (77.3%) non-crisis patients showed low IL-8 levels (less than 15 pg/ml). Healthy controls had low IL-8 levels. A significant difference in serum IL-8 levels was observed between crisis and non-crisis sickle cell patients (P<0.0001). There was no correlation between IL-8 levels and hematological data or hemoglobin patterns. High serum IL-8 levels were observed in VOC patients independently of the crisis-inducing factor. We conclude that in the studied population, IL-8 concentration may be a useful VOC marker, although the mechanism of the pathogenic process of sickle cell VOC syndromes remains unclear.